Perbandingan Kualitas Kertas Komposit dari Ampas Tebu dan Kertas Koran Berdasarkan Konsentrasi NaOH yang Berbeda - Shinta Damayanti; Entin Daningsih; Andi Besse Tenriawaru (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Paper is needed in large quantities so the need for wood as a raw material for paper is getting higher. Composite paper uses non-wood raw materials can be an alternative to make paper. Bagasse can be used as a substitute for wood fiber and reduce waste in the environment to make composite paper. Likewise, newsprint can be used as a mixture of composite paper. This study aims to compare the quality of composite paper from bagasse and newsprint mixtures using different concentrations of NaOH. The method was an experimental completely randomized design (CRD) consisting three treatments of NaOH (4, 6, and 8%) and 10 replications. The parameters measured were paper thickness, grammage, mass density, and tensile resistance, and were using SPSS ANOVA and continued with LSD test. Paper thickness is affected by the amount of cellulose that was degraded as well as paper grammage, paper thickness and grammage have higher values at the lowest concentration of NaOH (4%). Meanwhile, the tensile strength showed long cellulose had not been degraded much and resulted in higher tensile strength. This also resulted in mass density showing the highest density at the highest concentration of NaOH (8%). In conclusion, concentration of 4% NaOH resulted in paper thickness, grammage, and higher tensile strength compared to 6% and 8% NaOH concentrations. However, the highest mass density was influenced by 8% NaOH concentration compared to 6% and 4% NaOH concentrations.